Developing a Higher Performance and Less Thickness Concrete Pavement: Using a Nonconventional Concrete Mixture - Fady M. A. Hassouna; Yeon Woo Jung (Advances in Civil Engineering)
During the last three decades, concrete pavement or rigid pavement became a widely used alternative of flexible pavement (asphalt pavement) at freeways and highways with high traffic of heavy vehicles, due to its durability, long life, and less need of maintenance; however, the cost of construction for rigid pavement is very high compared to asphalt pavement. Developing a new concrete mixture to increase the performance and reducing the required thickness of concrete pavement became an important issue in rigid pavement design in order to reduce the high construction cost. In this study, a new concrete mixture was developed using specific amounts of steel fibers and steel slag (as a supplementary cementing material to replace a part of the cement). Several mixtures with different concentrations of fibers were prepared, and samples were tested for workability, early flexural strength, and ultimate flexural strength. The results showed that the new concrete mixture could achieve an increase in flexural strength between 48.9% and 50.5% compared to normal concrete mixture without steel fibers and steel slag, with minimum acceptable workability, and therefore, the required pavement thickness could be decreased by more than 24%.